(untitled) (Physical Education, Health and Social Sciences, 2025)
This research investigates the linguistic, cultural, and stylistic transformations that occur when English novels are translated into Urdu. It examines how translators negotiate meaning between two literary and cultural systems that differ in idioms, metaphors, and worldviews. Grounded in Nida’s theory of Dynamic Equivalence and informed by the perspectives of Bassnett, Lefevere, Venuti, and prominent Urdu scholars such as Jameel Jalibi, Gopi Chand Narang, and Shamsur Rahman Faruqi, the study employs a mixed-methods approach combining textual, thematic, and discourse analyses with reader surveys and translator interviews. The findings reveal that Urdu translations frequently employ adaptive strategies such as domestication, cultural substitution, and idiomatic modification to preserve the emotional and contextual impact of the original text. These transformations enhance readability and cultural relevance while maintaining narrative integrity. The research concludes that English–Urdu translation is a creative and interpretive act that fosters cross-cultural dialogue, expands Urdu’s literary scope, and enriches both linguistic traditions.